Asprosin Can Have a Beneficial Influence on Male Rats' Sexual Behaviour - Ozdede, M. R.; Oz, Z. D.; Ucer, A.; Yalcin, T.; Orhan, S. U.; Yasar, A.; Kelestimur, H. (Wiley, 2022)
[Abstract Not Available]